Psychosocial functioning of young adults with cystic fibrosis and their families. Issue 8 (August 1994) - Blair, C; Cull, A; Freeman, C P
Abstract : BACKGROUND--The psychosocial functioning of adolescents and young adults with cystic fibrosis still living in the parental home was investigated. With its proven genetic aetiology cystic fibrosis is an ideal model with which to assess the impact of a chronic and life threatening disorder on family and individual psychological and social functioning. METHODS--Twenty nine patients with cystic fibrosis and their families were compared with those of 27 patients with anorexia nervosa and 31 well controls. Assessments were made using self reporting, interview, and observational methods. RESULTS--Most patients with cystic fibrosis were in robust psychological health and only differed from their healthy peers in that they were much less likely to be in employment. Mothers of patients with cystic fibrosis or anorexia nervosa were more likely than the mothers of the well group to be emotionally distressed, although this was not so for fathers. Young people in both illness groups were more likely to have parents with high levels of expressed emotion. Most families of patients with cystic fibrosis had good problem solving abilities. CONCLUSIONS--In spite of the burden of illness in cystic fibrosis psychological functioning in many respects matches that of well young people.